Scaling Out Climate-Smart Agriculture for Resilient Farming in Adilabad District of Telangana - Indian Council of Agricultural Research; International Water Management Institute; CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Climate-smart agriculture (CSA) is an important approach towards minimizing impacts due to climate risks and maintaining agricultural growth. This report is part of the project that aims to contribute towards building a national strategy for scaling out climate resilient agricultural practices and technologies by synthesizing cumulative knowledge, experiences, and learnings gained by ICAR, CCAFS, and CG Centre’s Programs in climate risk management. The report outlines the process of developing a district level adaptation plan for resilient farming in the Adilabad district of Telangana by following steps of climatic risks characterization, identification and prioritization of CSA technologies and practices, the convergence of government policies and programs. Dry spell, uneven rainfall, heat wave and cold wave frequently occur in the district with severe impact on the rainfed cropping system in the district. Location specific CSA practices have the potential to reduce the losses due to climate risk. Potential CSA technologies are categorized into six main categories of water-smart, energysmart, nutrient-smart, carbon-smart, weather-smart and knowledge-smart. Area specific suitable CSA technologies are identified following a participatory approach through stakeholder’s participation. The identified list of technology is evaluated and prioritized for implementation feasibility, acceptability, adoption barriers, synergy with government plans, incentive mechanisms and key institutions. For the implementation of these technologies at the district level, the total estimated budget was estimated to be Rs. 273.0 Crore. The convergence of resources from relevant government schemes/projects for mobilizing funds for prioritized CSA technologies has been proposed for implementing climate adaptation plans at the district level. This integrated framework will be useful for the investment decision making process for resilient farming.